Efforts to Improve the Economy of the Ambulu District Community Through the PNM Ulamm Institution in Financial Management - Safrizal, Safrizal; Ningrum, Kristina Ayu; Purwanti, Yuniasih; Nasihin, Ihsan (Sekolah Tinggi Ilmu Ekonomi Mahaputra Riau, 2025)
The aim of this research is to provide an overview of how influential PNM ULaMM is in improving the economy of Ambulu sub-district. The Micro Capital Services Unit (ULaMM) is a service from PT Permodalan Nasional Madani (PNM) which was formed by the government with the aims and objectives of empowering micro and small businesses. One of them is in Ambulu District which needs capital for business, and existing micro-entrepreneurs to develop their businesses. This research aims to describe efforts to improve micro businesses in the area of financial management. The research results show that through this activity, the community experiences increased financial capacity, business growth and overall economic prosperity. Therefore, this research provides an important contribution to understanding the role of microfinance institutions in supporting efforts to improve the community economy at the local level. The implications of these findings can be a reference for related parties, including other micro institutions, to develop more effective strategies in improving the economic welfare of communities in similar areas. To obtain financing from the PNM ULaMM institution, the community does not need to be complicated by the requirements they have to fulfill as with banking institutions